Bentham's Metaphysics and the Science of Divinity - Crimmins, James E. (Harvard theological review, 1986)
The utilitarian philosopher Jeremy Bentham (1748–1832) has long been recognized as an exponent of a new science of society. However, scholars of his thought have given scant attention to at least one important aspect of that science: the relationship between the metaphysical presuppositions of his social science and his view on religion. Rarely is it considered that Bentham's aspiration to create a science of society in emulation of physical science was fundamental to his critique of religion just as it was to all other areas of his thought. This critique of religion was set out principally in a series of works written between the years 1809 and 1823. Swear Not at All was published in 1817, and followed a year later, after earlier efforts were aborted in 1809 and 1813, by Church-of-Englandism and its Catechism Examined. The Analysis of the Influence of Natural Religion on the Temporal Happiness of Mankind appeared in 1822 and Not Paul, but Jesus in 1823. It was not merely a coincidence that in the very period when Bentham devoted so much of his time to religion his work on metaphysics and logic substantially reached fruition. The “Book on Logic,” on which Bentham worked at intervals between 1811 and 1821, was intended to give a full description of his “method.” The work was never completed but was eventually edited and included in several fragments in John Bowring's edition of The Works of Jeremy Bentham. The essay on “Nomography” with an appendix on “Logical Arrangements, or Instruments of Invention and Discovery Employed by Jeremy Bentham” is included in the third volume, and in the eighth volume is to be found the “Essay on Logic,” “A Fragment on Ontology,” the “Essay on Language,” and the “Fragments on Universal Grammar.” The metaphysics described in these essays by Bentham was initially developed by him during the formative years of his intellectual life in the early 1770s, and he was always aware of its particular consequences in the field of religion.